Mahatma Gandhi : a biography - Nanda, B. R. (Oxford University Press, 1989)
This now-classic biography of the great Indian leader not only recounts the events of his life but also offers a panoramic view of Indian history during the first half of the 20th century. Nanda focuses particularly on Gandhi's philosophy and views on non-violence, religion, sex, economics, and communism.